Collective action, social capital and group lending - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
For low-income households with meager assets, financial services that could potentially augment their income are of extreme importance. Financial mechanisms that could facilitate asset buildup, protect against risks, and sustain livelihoods of poor people would go a long way in improving their living conditions and social status. Microfinance is one such financial mechanism that caters to poorer and marginal households and communities.